Renal Nerve Deafferentation Attenuates the Fall in GFR during Intravenous Infusion of Furosemide in Anesthetized Rats - Magali Araujo; Glenn Solis; William J. Welch; Christopher S. Wilcox (Karger Publishers, 2020)
Introduction: Furosemide reduces the glomerular filtration rate (GFR) and increases the renal vascular resistance (RVR) despite inhibiting tubuloglomerular feedback but increases proximal tubule pressure, renin release, and renal nerve activity. Objective: This study tested the hypothesis that the fall in GFR with furosemide is due to volume depletion or activation of angiotensin type 1 (AT1) receptors or renal nerves. Methods: Furosemide was infused for 60 min at 1.0 mg·kg−1·h−1 in groups of 5-8 anesthetized rats. Additional groups received intravenous volume replacement to prevent fluid and Na+ losses or volume replacement plus losartan or plus sham denervation or plus renal denervation or renal nerve deafferentation. Results: At 60 min of infusion, furosemide alone reduced the GFR (-37 ± 4%; p < 0.01). This fall was not prevented by volume replacement or pretreatment with losartan, although losartan moderated the increase in RVR with furosemide (+44 ± 3 vs. +82 ± 7%; p < 0.01). Whereas the GFR fell after furosemide in rats after sham procedure (-31 ± 2%), it was not changed significantly after prior renal deafferentation. Proximal tubule pressure increased significantly but returned towards baseline over 60 min of furosemide, while urine output remained elevated, and GFR and renal blood flow depressed. Conclusions: The fall in GFR over 60 min of furosemide infusion is independent of volume depletion or activation of AT1 receptors but is largely dependent on renal afferent nerves.